The significance of cell‐related challenges in the clinical application of tissue engineering. Issue 12 (16th August 2016) - Almela, Thafar; Brook, Ian M.; Moharamzadeh, Keyvan
Abstract: Tissue engineering is increasingly being recognized as a new approach that could alleviate the burden of tissue damage currently managed with transplants or synthetic devices. Making this novel approach available in the future for patients who would potentially benefit is largely dependent on understanding and addressing all those factors that impede the translation of this technology to the clinic. Cell‐associated factors in particular raise many challenges, including those related to cell sources, up‐ and downstream techniques, preservation, and the creation of in vitro microenvironments that enable cells to grow and function as far as possible as they would in vivo. This article highlights the main confounding issues associated with cells in tissue engineering and how these issues may hinder the advancement of therapeutic tissue engineering. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 3157–3163, 2016.